Spatiotemporal distribution patterns of soil nematodes along an altitudinal gradient in the cold temperate zone of China - Fangyuan Shen; Chen Chen; Yan Zhang; Li Ji; Huifeng Liu; Lixue Yang (Global Ecology and Conservation, 2023)
As important components of the cosmopolitan soil biota, soil nematodes are found at multiple trophic levels of the belowground food web and play an important role in soil function. Exploring the actual patterns of soil nematodes along the altitudinal gradients helps understand the spatial soil ecology. In this study, we used molecular analysis approaches to reveal the soil nematode spatiotemporal changes on Oakley Mountain in the northern Greater Khingan Mountain Ranges Northeast China. Our results showed that although the alpha diversity of nematode communities generally decreased with the increased altitude, it did not exhibit a monotonic decrease pattern. Bacterial feeding nematodes occupied the largest proportion among all nematode feeding types. Altitude had a more significant effect than soil depth on the structure of nematode community in all seasons. Soil bulk density, moisture, dissolved organic carbon, temperature, pH, nitrate nitrogen, and total phosphorus were the significant soil variables driving the composition of nematode community. The co-occurrence networks of soil nematode communities showed a distinct seasonal pattern. The nematode community networks in May and September had more modes and links, higher average degrees, and higher average clustering coefficients than the network in July. We demonstrated that the variance of nematode community structure in different altitudes and soil depths could be well explained by edaphic factors. This study extends our knowledge of the nematode spatial ecology in cold temperate regions and contributes to further investigation of soil ecological processes in global challenges.